IMPORTANCE OF PRAKRITI IN MAINTAINANCE OF HEALTH - Goswami Chandani; Vyas Mahesh; Baghel Arjunsinh; Vyas Hitesh (International Journal of Applied Ayurved Research, 2017)
Prevention of health is one of the most important issues for medical sciences in present era. Ayurveda has lot to contribute in this sector. The concept of Prakriti is such a concept which can be used for this purpose. This concept deals with physical, mental, social and spiritual aspects which in turn define health. In Samhita concepts of Dinacharya, Rutucharya, Aaharvidhivisheshayatan, Aaharvidhi etc. are described. They are key points to maintain health, as they have direct impact over human physiology. Implementation of them in daily regimen according to Doshik dominancy soothes individual’s lifestyle. Each season have its dominant Rasa and Guna which affects differently to the different Prakriti persons. Swasthavritta varies according to Prakriti in every individual; for example, the dietary regimen and exercises for Vata Prakriti are entirely different than those of Pitta and Kapha Prakriti. The awareness about the Prakriti and lifestyle accordingly will definitely help to improvise one’s own health. This particular work elaborates the relation among Prakriti, Aahar, Vihar, Dincharya and Kaala in relation to maintenance of health.